(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
An alternative approach to manage fish health that is fast gaining attention in the aquaculture industry is probiotics, a microbial intervention approach. Probiotics have shown that they can help to increase fish growth by enhancing the feed conversion efficiency, as well as confer protection against harmful bacteria by different modes of action. The present paper shows the current knowledge of the use of probiotics in aquaculture, particularly focusing on their modes of action such as spatial and nutritional emulation, inhibitory metabolites, immunomodulation and stress-alleviating mechanism. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 105-109, 2018